Need Assesment Dalam Pengembangan Lembar Kerja Peserta Didik Elektronik (E-Lkpd) Berbasis Pendekatan Deep Learning Pada Materi Klasifikasi Makhluk Hidup Kelas X Sma - Kasih Maylani; Ummi Kalsum; Nurkhairo Hidayati (CV. SINAR HOWUHOWU, 2026)
This study aimed to analyze the need for developing an electronic student worksheet (E-LKPD) based on a deep learning approach for the topic of living organism classification in Grade X senior high school. The research employed a descriptive quantitative method and was conducted at SMA Negeri 3 Siak Hulu, involving one biology teacher and 38 students of Grade X MIPA. Data were collected through observation, teacher interviews, and student questionnaires. Interview data were analyzed descriptively using qualitative techniques, while questionnaire data were analyzed quantitatively by calculating the percentage of needs. The results showed that the need for learning media reached the very high category with a percentage of 83%, media suitability to student characteristics was 76%, availability and benefits of learning media at school were 77%, and expectations toward deep learning-based E-LKPD reached 82%. Teacher interview results supported the questionnaire findings, indicating that digital learning media are essential to enhance students’ motivation, learning independence, and conceptual understanding in Biology. Therefore, it can be concluded that the development of a deep learning-based E-LKPD on living organism classification is highly necessary to support more effective, interactive, and meaningful biology learning.